Evaluating A Mid School Program in Bekasi: The Building Learning Power - Yayat Suharyat; Ibnu Muthi; Haswani Haswani (AL-ISHLAH: Jurnal Pendidikan, 2022)
The Building Learning Power program aims to optimize all student capacities in developing cognitive and soft skills aspects as well as designing and realizing students' short-term and long-term goals. This research is evaluative research with the CIPP evaluation model which includes four pillars, namely: Context, Input, Process, and Product. This study aims to determine the success of the program Building Student Learning Power. The results of the study are as follows: 1) Context evaluation shows that this program is very much needed by students to improve self-ability and soft skills, 2) input evaluation shows that the input of teachers, students and infrastructure is in a good category, 3) process evaluation is in a good category, but obstacles in program implementation still need to be overcome, 4) product assessment in the good category. In short, the achievement program to build learning power must continue to be improved because the benefits of the program can be felt by students and parents. Even though, there are some aspects that have not been achieved in each pillar of daily activities needed to be improved.